2017
DOI: 10.1080/00071668.2016.1262004
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying sperm egg interaction to assess the breeding efficiency through artificial insemination in guinea fowls

Abstract: 1. Guinea fowl hens were inseminated weekly once with two doses of spermatozoa (75 million and 100 million) in two different diluents, Beltsville poultry semen extender (BPSE), and Instruments for Veterinary Medicine (IMV), each with and without pre-insemination vaginal douching. Per cent fertility, hatchability, dead germ, dead in shells along with data on sperm egg interaction and vaginal microbial counts were recorded. 2. Artificial insemination had significantly improved the per cent fertility and hatchabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…These semen parameters decreased as dilution rates increased. Comparable observations were reported by Hudson (2015), who reported superior sperm motility at lower dilution rates (1:2 and 1:3) in semen extended using BPSE and IMV diluents. Furthermore, Bonato et al (2021) found that as the dilution rate increased, the proportion of normal and abnormal living spermatozoa decreased.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These semen parameters decreased as dilution rates increased. Comparable observations were reported by Hudson (2015), who reported superior sperm motility at lower dilution rates (1:2 and 1:3) in semen extended using BPSE and IMV diluents. Furthermore, Bonato et al (2021) found that as the dilution rate increased, the proportion of normal and abnormal living spermatozoa decreased.…”
Section: Discussionsupporting
confidence: 77%
“…These observations are in agreement with those reported in guinea fowl semen diluted using Lake Semen Extender (LSE), Modified Beltsville Poultry Semen Extender (MBPSE) and Beltsville Poultry Semen Extender (BPSE) (Keerthy 2016); Helmeted guinea fowl semen diluted using powdered coconut water (Lavor et al 2012); Philippine local chicken semen diluted using AU and Lake's Low Temperature (LLT) extenders (Antalan et al 2015); and Bagladeshis native chicken diluted using Lake A and Lake B diluents (Das et al 2016). In addition, similar outcomes were also reported elsewhere (Mohan et al 2013;Hudson 2015). The decrease in spermatozoa motility, percentage of live spermatozoa, and morphologically normal spermatozoa over the storage period may be because sperm metabolites are released, changing the nutritional composition of the medium (Keerthy 2016).…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, on postmortem some lesions of injuries in reproductive tracts were noticed. These lesions might be of the glass straw used to deposit semen or of forceful vaginal douching that is vital, unavoidable, but hygienically chancy segment of AI (Hudson et al, 2017). These results are similar to the findings of Yan Li et al (2018) who also found much higher average weekly mortality in females subjected to AI as compared to hens which were allowed to inseminate naturally.…”
Section: Effects Of Different Mating Strategies On Productive Performsupporting
confidence: 80%
“…AI is extensively used in turkeys [ 114 ]. AI improved percentage hatchability and fertility compared to natural mating in guinea fowl [ 115 ]. A greater number of fertilized eggs was obtained in broiler breeder hens after application of AI [ 116 ].…”
Section: Methods To Improve Reproductive Efficiency Of Gandersmentioning
confidence: 99%